EFFECT OF IMAGE MATCHING WINDOW SIZE ON SATELLITE JITTER FREQUENCY DETECTION - H. Zhang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
Satellite attitude jitter is a common and complex phenomenon for high-resolution satellites and it is detectable by multi-temporal image matching. This paper analyses the effect of image matching window size on jitter frequency detection. First, two simulation images with a given short time lag and line scanning frequency affected by a modelled jitter are generated based on the principle of dynamic imaging model. Then, the relative image distortions are obtained by dense image matching with different matching window size and the frequency is estimated through spectrum analysis of the obtained image distortions. The experimental results demonstrated the feasibility and reliability of high frequency jitter detection based on dense image matching, and the results indicated that the maximum detectable frequency is almost not affected by the change of image matching window size, which provided useful demonstration of image-based satellite jitter detection capacity.